Ethics and international relations : a tragic perspective - Lebow, Richard Ned (Cambridge : Cambridge University Press, 2020)
Lebow demonstrates that foreign policies consistent with generally accepted ethical norms are more likely to succeed, and those at odds with them to fail. Constructing original data sets and analyzing multiple case studies, Lebow makes an empirical case for ethics in international relations. His approach looks to create a productive dialogue between those who ask primarily 'ought' questions and those who pose 'is' questions. The former want to establish appropriate criteria for the behaviour of state and non-state actors and the discourses that lead to their policy decisions, whereas scholars who pose 'is' questions are concerned with how political actors behave and the principles and assumptions that might explain their behaviour. Lebow bridges the gap between 'is' and 'ought' questions by making an instrumental argument in favour of ethical foreign policy. He examines policymaking as well as policy, offering ethical guidelines for policymaking that are likely to result in more successful policies.
Introduction -- Tragedy -- Crime and punishment -- Successful foreign policies -- Policymaking -- Conclusions.
Title from publisher's bibliographic system (viewed on 21 Sep 2020).
Keywords: International relations -- Moral and ethical aspects